2012
DOI: 10.1186/1471-2334-12-100
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 low-level viraemia assessed with 3 commercial real-time PCR assays show high variability

Abstract: BackgroundCurrent real-time PCR-based HIV-1 viral load (VL) assays allow the detection of residual viraemia in antiretroviral-treated patients. The clinical outcome of HIV1 patients experiencing low-level replication (<50 cop/mL) in comparison with fully suppressed patients is currently debated. We analysed variability of 3 VL assays <50 cop/mL, and evaluated the reproducibility of viral blips <100 cop/mL.MethodsThree commercial VL assays were tested: Versant HIV-1 RNA 1.0 kPCR (Siemens), Abbott Realtime HIV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 17 publications
(19 reference statements)
4
43
0
Order By: Relevance
“…We found that the Amplicor assay underreported pVL around its LLOQ. This is consistent both with other findings of assay variability at low pVL 14 and with the observation that switching from the Amplicor to the Taqman 1 assay (40 copy/ml LLOQ) led to increased observation of blips. 1 Of greater concern than issues of assay accuracy per se was that blip detection can imply that pVL is consistently high in the 50 to 300 copy/ml range (Fig.…”
supporting
confidence: 80%
“…We found that the Amplicor assay underreported pVL around its LLOQ. This is consistent both with other findings of assay variability at low pVL 14 and with the observation that switching from the Amplicor to the Taqman 1 assay (40 copy/ml LLOQ) led to increased observation of blips. 1 Of greater concern than issues of assay accuracy per se was that blip detection can imply that pVL is consistently high in the 50 to 300 copy/ml range (Fig.…”
supporting
confidence: 80%
“…Furthermore, there have been reports that real-time PCRbased assays tend to identify more patients as having low-level viremia than does the Amplicor test (10)(11)(12)(13)(14)(15). Multiple studies have documented variation between these assays when measuring samples with low viral load levels (6,13,(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Therapy outcomes have been shown to be influenced by lowlevel viremia in some studies (16,(22)(23)(24)(25)(26)(27)(28) but not others (29)(30)(31)(32), in part reflecting differences in the measured outcomes. However, the overall clinical relevance of low-level viremia remains controversial.…”
mentioning
confidence: 99%
“…In addition, recent studies assessed the correlation between paired assay results at low viral loads (including the assays examined here) and found that the correlation between assays was lower at lower HIV-1 RNA results and that discordance decreased when a 200-copies/ml threshold was used versus a 50-copies/ml threshold (9, 10). These findings were not completely unexpected, based on previous studies that evaluated sources of variability in HIV-1 RNA assays (11)(12)(13), including the variability at the low end of the reportable range (14). Limit of detection for an assay refers strictly to the ability of an assay to detect the HIV-1 RNA in a sample with a Ͼ95% detection rate.…”
Section: Discussionmentioning
confidence: 99%